Anomalies in Family Planning in Central Java, Indonesia - Wilonoyudho, Saratri; Prajanti, Sucihatiningsih Dian Wisika (Universitas Negeri Semarang, 2018)
This study was aimed at uncovering the anomalies in the implementation of the Population, Family Planning and Family Development Program in Central Java province. Qualitative-naturalistic approach was employed. The results of the study about the population and family planning in Central Java Province is showed an alarming rate of TFR (Total Fertility Rate) indicator of 2.3 to 2.5. In addition, the public mind set about the ideal number of children in a family also increased from the TFR indicator of 2.6 to 2.8. This mindset would hinder family planning program. To overcome the anomalies, BKKBN Central Java Province made various strategic efforts. The high rate of CPR (Contraseptive Prevalence Rate) which was not followed by the low rate of TFR was assumed to be related to the active family planning participants were not using long term contraception method, leaving them vulnerable to drop out. Therefore, an increase in long term contraception method, would be a top priority in the population and family planning program in Central Java. In the